2008
DOI: 10.1007/s10935-007-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

E-technology and Pedometer Walking Program to Increase Physical Activity at Work

Abstract: This study examined the application of the transtheoretical model (TTM) as a means to increase physical activity at the worksite through the introduction of a 10-week pedometer walking program combined with internet-based motivational messages. Participants (N = 206) were employees of two worksites who completed a health history questionnaire and assessment based on the TTM. There were significant improvements in the number of steps per week, level of physical activity, movement through stage of change and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 35 publications
7
73
1
1
Order By: Relevance
“…Direct comparison of our results with those in the cited reviews is discouraged due to our decision to focus only on interventions that could be implemented during productive work, with the intention to change the behavior of the individual while working. Notably, the six multi-component PA interventions included in our review (52,70,72,(74)(75)(76) were not more effective than the interventions with individualized initiatives only (69,73,77).…”
Section: Personalized Behavioral Interventionsmentioning
confidence: 77%
See 1 more Smart Citation
“…Direct comparison of our results with those in the cited reviews is discouraged due to our decision to focus only on interventions that could be implemented during productive work, with the intention to change the behavior of the individual while working. Notably, the six multi-component PA interventions included in our review (52,70,72,(74)(75)(76) were not more effective than the interventions with individualized initiatives only (69,73,77).…”
Section: Personalized Behavioral Interventionsmentioning
confidence: 77%
“…Direct comparison of our results with those in the cited reviews is discouraged due to our decision to focus only on interventions that could be implemented during productive work, with the intention to change the behavior of the individual while working. Notably, the six multi-component PA interventions included in our review (52,70,72,(74)(75)(76) were not more effective than the interventions with individualized initiatives only (69,73,77).As for SB, three out of six studies included components specifically targeting a reduction of SB (71,74,77), and only two found a significant effect (71,77). In a review of interventions specifically targeting PA, Chau et al (34) argued that PA interventions do not necessarily reduce SB.…”
mentioning
confidence: 81%
“…Previous research on selfmonitoring and stage of change has shown an increase in stage of change as selfmonitoring behavior increases. A popular form of self-monitoring, pedometer use, has been used in walking interventions where pedometer users successfully reached a higher stage of change from pre to post intervention (Faghri et al, 2008;Myers, Ronero, Anzaldua, & Trinidad, 2011). Another possibility is that self-monitoring is useful for people in earlier stages of change (i.e., precontemplation and contemplation) and less useful as activity increases.…”
Section: Discussionmentioning
confidence: 99%
“…As an outcome of the health, physical activity also has a significant effect in creating healthy living, safety, and mental and social welfare for the people and societies. The establishment of a healthy and happy society needs the effort of healthy, efficient, and intellectual labor forces [4]. Due to importance of the regular physical activity in creating and maintaining the health, this behavior has been listed as one of the 15 priorities to change the health recovery behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Due to importance of the regular physical activity in creating and maintaining the health, this behavior has been listed as one of the 15 priorities to change the health recovery behavior. Furthermore, scientific observations have shown that the physical activity can be very influential in health in all ages [2][3][4]. According to results of 27 meta-analysis conducted by the world health organization, regular physical activity can be very effective in reducing 35-55% of cardiac infarction cases and it can also decrease the rate of mortality.…”
Section: Introductionmentioning
confidence: 99%